Hashtags as pragmatic devices of cultural reproduction in digital discourse - Galina E. Snezhko (Training, Language and Culture)
Hashtags are high-visibility linguistic constructs that promote cultural alignment and index ideological stances in digital environments. Although hashtags are becoming more and more popular among academics as online communication tools, little is known about how they contribute to the practical reproduction of cultural norms. Few research has looked at the language processes by which these values are passed down or reframed, despite the fact that sociological theories of cultural reproduction have long studied how customs and norms endure over generations. This study intends to fill this gap, to which end it examines how hashtags serve as practical language tools in the reproduction of cultural values in online conversation. The study uses a qualitative-pragmatic discourse analytic framework to address this question and utilises information from indexicality theory, digital discourse analysis, and language pragmatics. A multi-step interpretative approach was used to examine a deliberately and theoretically collected dataset of 90 English-language social media postings (January 2020–March 2025), which included 288 thematically significant hashtags. Indexicality, framing, pragmatic function, and presupposition were among the analytical categories. The results show that hashtags are used to index identification and ideological alignment, encode stance, and assume common cultural knowledge. Hashtags served as framing mechanisms that placed the user inside cultural narratives, and many posts featured binary oppositions (such as tradition vs. modernity). Notably, hashtags also made it easier to engage with conventional values in a critical and sarcastic way, which proved their ability to both reproduce and challenge cultural norms. According to the study’s findings, hashtags are pragmatically dense units that contribute to the perpetuation of cultural norms in online conversation. They serve as symbolic tools of continuity and emphasise the crucial function that language use in context plays in contemporary processes of social identity construction and cultural transmission.